Tumour necrosis factor- released by testicular macrophages induces apoptosis of germ cells in autoimmune orchitis - Theas, Maria Susana (2008)
BACKGROUND: Experimental autoimmune orchitis (EAO) is a model of chronic inflammation and infertility useful for studying testicular immune and germ cell (GC) interactions. In this model, EAO was induced in rats by immunization with testicular homogenate and adjuvants; Control (C) rats were injected with adjuvants. EAO was characterized by an interstitial infiltrate of lymphomonocytes and seminiferous tubule damage, moderate 50 days (focal orchitis) and severe 80 days after the first immunization (severe orchitis). Based on the previous results showing that the number of macrophages and apoptotic GC expressing tumour necrosis factor (TNF) receptor 1 increased in EAO, we studied the role of macrophages and TNF-a in GC apoptosis. METHODS AND RESULTS: Conditioned media of testicular macrophages (CMTM) obtained from rats killed on Days 50 and 80 decreased the viability (MTS, P < 0.01) and induced apoptosis (terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick end labelling,TUNEL) of GC obtained from EAO but not from non-immunized, N rats (P < 0.001). TNF-a content (enzymelinked immunosorbent assay) was significantly higher in the CMTM from EAO versus C rats on Day 80 (P < 0.05). The apoptotic effect of CMTM from Day 80 rats was abrogated by a selective TNF-a blocker (Etanercept). Moreover, TNF-a in vitro induced GC apoptosis. TNF-a expression (by immunofluorescence) was observed in testicular (ED2+) and non-resident (ED1+) macrophages, the percentage of TNF-a+ macrophages being similar in focal and severe orchitis. CONCLUSIONS: Results demonstrated that soluble factors released from testicular EAO macrophages induce apoptosis of GC, biased by the local inflammatory environment, and that TNF-a is a relevant cytokine involved in testicular damage during severe orchitis.